Factors Influencing the Quality of Services at the Pharmacy Installation of Pagar Jati Public Health Center - Nurainun Badriani; Barita Aritonang; Abdi Lestari Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
The quality of pharmaceutical services plays a vital role in supporting effective healthcare delivery at the primary care level. High quality pharmacy services contribute to patient safety, treatment effectiveness, and overall satisfaction with healthcare experiences. This study aims to analyze the factors influencing the quality of pharmacy services at the Pharmacy Installation of Puskesmas Pagar Jati, specifically examining human resources, infrastructure, drug management, and patient satisfaction.This research applied a quantitative approach with a cross-sectional design. A total of 96 respondents were selected using purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire and analyzed through multiple linear regression and logistic regression tests.The results show that drug management has the most dominant influence on service quality (p = 0.002; OR = 15.984), followed by human resources (p = 0.036; OR = 3.767). Patient satisfaction showed a nearly significant influence (p = 0.058), while infrastructure did not show a statistically significant effect (p = 0.728). The study concludes that the improvement of pharmacy service quality is more determined by process-related aspects, particularly drug management systems and the competency of pharmacy personnel